New Economy Stock Valuations and Investment in the 1990s - Sloek, Torsten (IMF Working Papers; Working Paper ;, 2001)
This paper investigates whether there is a different impact from changes in "new" and "old" economy stock valuations on private investment for seven OECD economies. A vector autoregressive model is estimated for each individual country, using quarterly data over the period 1990-2000. We find that the impact from changes in valuations of new economy stocks to investment is roughly the same in North America and United Kingdom as in continental Europe. By contrast, the impact from changes in old economy stock valuations on investment is, in general, larger in North America and United Kingdom than in continental Europe. Finally, the results suggest that in continental Europe the impact on investment from changes in the valuation of new economy stocks is bigger than for old economy stocks, whereas for North America and United Kingdom the impact is more similar.